2010
DOI: 10.1108/20425961201000023
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge management in creating and sustaining high performance organisations: The case of financial institutions in Uganda

Abstract: The study described in this paper develops an evaluation model aimed at investigating the relationships between knowledge management and objective and perceived organizational high performance. Design/methodology/approach: A comprehensive review of theory, research and practices on knowledge management and high performance develops a model that forms the basis of the study. The model was operationalised in financial institutions in Uganda, and was used as the basis to develop the hypotheses that are tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…Depending on organizational goals, different methods are adopted by different firms to measure their performance. This performance indicator can be measured in financial and non-financial terms (Darroch, 2005;Bagorogoza and Waal, 2010;Bakar and Ahmad, 2010). Most firms, however, prefer to adopt financial indicators to measure their performance (Grant et al, 1988;Hoskinson, 1990).…”
Section: Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on organizational goals, different methods are adopted by different firms to measure their performance. This performance indicator can be measured in financial and non-financial terms (Darroch, 2005;Bagorogoza and Waal, 2010;Bakar and Ahmad, 2010). Most firms, however, prefer to adopt financial indicators to measure their performance (Grant et al, 1988;Hoskinson, 1990).…”
Section: Firm Performancementioning
confidence: 99%
“…Return on assets (ROA) (Zahra, 2008), average annual occupancy rate, net profit after tax and return on investment (ROI) (Tavitiyaman et al, 2012) are the commonly used financial or accounting indicators by firms. Some other common measures are profitability, productivity, growth, stakeholder satisfaction, market share and competitive position (Garrigos- Simon and Marques, 2004;Marques et al, 2005;Bagorogoza and Waal, 2010). However, financial elements are not the only indicator for measuring firm performance.…”
Section: Firm Performancementioning
confidence: 99%
“…Mohamad et al (2015) professed that performance could measure with quantitative or qualitative or both form. Similarly, firm performance can be measured by nonfinancial and financial methods too (Bagorogoza & Waal, 2010;Bakar & Ahmad, 2010). Santos and Brito (2012) discussed in their paper that the three authors, Combs, Crook, and Shook (2005) analyzed 238 articles which were published between 1980 and 2004 and found that 56 different indicators of financial performance.…”
Section: Microenterprise Business Performance and Theory Of Profitmentioning
confidence: 99%
“…These measures of performance can be quantitative or qualitative or both. Similarly, firm performance can be measured by non-financial and financial methods (Bagorogoza & Waal, 2010;Ahmad, Ramayah, Wilson, & Kummerow, 2010;Bakar & Ahmad, 2010). Previous researchers have suggested that financial measures should have a link with market-based measures (Dess & Davis, 1984;Hambrick & Mason, 1984;Schendel & Patton, 1978).…”
Section: Smes' Performancementioning
confidence: 99%
“…However, most of the organisations adopt the quantitative measurement to evaluate their firm performance. Moreover, the measures of firm performance could be financial and non-financial (Bakar & Ahmad, 2010;Ahmad, Ramayah, Wilson, & Kummerow, 2010;Bagorogoza & Waal, 2010). Performance measurement for this study uses the financial technique.…”
Section: Measurement Of the Variablesmentioning
confidence: 99%